PENGARUH KONVERGENSI IFRS, KOMITE AUDIT, DAN KOMPLEKSITAS PERUSAHAAN TERHADAP FEE AUDIT - Willy Suryajaya Yulio (Jurnal Akuntansi Bisnis, 2016)
This research analyzes the factors that influence the determination of the external audit fee on all companies listed on the Indonesian Stock Exchange (BEI) 2010-214. The research used secondary data from the annual reports of all companies listed on the Indonesian Stock Exchange (IDX) from 2010 to 2014. Sampling method used in this study was purposive sampling. A total sample of 186 companies were used in analysis. The data is analyzed using multiple linear regression analysis. Factors to be tested in this study include IFRS Convergence, Interaction Skills Frequency meeting with the Audit Committee, the Audit Committee Number and Complexity of the Company. Results from this study showed that the amount and complexity of the Company's Audit Committee has a significant positive effect on external audit fees. While IFRS convergence, Frequency Interaction Skills Audit Committee Meeting with no effect on external audit fees.